Profile of scientific productions on judo: an analysis of the Web of Science database (1956-2019) - Reis, F. D. G.; Franchini, E.; Capraro, A. M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Problem and aim. Judo is one of the most popular combat sports in the world. An evaluation of the presence of scientific knowl- edge, for example, using the Sport Policy Factors Leading to International Sporting Success (SPLISS) model, is necessary to develop high-performance sport. The objective of this work was to map the scientific articles on judo catalogued in the Web of Science platform. Material and Method. We analyzed variables such as the distribution of these articles by year; distribution by field of knowledge as set by the Web of Science platform; scientific journals that published the most on the subject; countries with the highest number of publica- tions; funding agencies that promoted the most research; articles with the most citations; and words most frequently cited as keywords. Results. In total, 637 articles published between 1956 and 2019 were analyzed. These works generated an h-index of 42, with an average of 12.7 citations per article. In addition, 75.3% of the studies were published between 2010 and 2019, and 62.9% are cata- logued in the Sport Sciences field. In all, 191 journals published research on judo. Brazil published 25.1% of these articles, followed by Poland, with 17.7%. Conclusions. It was found that there were two milestones for the increased number of research papers published. The first is linked to the inclusion of judo in the 1972 Olympic Games. The second is related to two factors: the overall global increase in scientific publi- cations, and the interest of researchers, for example, Brazilians and Poles, who have adopted this subject as a relevant object of study.